Optimization of polymer nanocomposite properties - Mittal, Vikas (Weinheim : Wiley-VCH, 2010)
A one-stop resource for researchers and developers alike, this book covers a plethora of nanocomposite properties and their enhancement mechanisms. With contributors from industry as well as academia, each chapter elucidates in detail the mechanisms to achieve a certain functionality of the polymer nanocomposite, such as improved biodegradability, increased chemical resistance and tribological performance. Special emphasis is laid on the interdependence of the factors that affect the nanocomposite properties such that readers obtain the information necessary to synthesize the polymer materials.
Optimization of Polymer Nanocomposite Properties; Contents; Preface; List of Contributors; 1: Polymer Nanocomposites: Synthesis, Microstructure, and Properties; 2: Morphology Development in Thermoset Nanocomposites; 3: Morphology and Interface Development in RubberClay Nanocomposites; 4: Morphology Development in Polyolefin Nanocomposites; 5: Rheological Behavior of Polymer Nanocomposites; 6: Mechanical Property Enhancement of Polymer Nanocomposites; 7: Stress Transfer and Fracture Mechanisms in Carbon Nanotube-Reinforced Polymer Nanocomposites.
Includes bibliographical references and index.
Print version record.
Keywords: Nanostructured materials; Polymeric composites; Nanostructured materials -- Properties; Polymeric composites -- Properties; TECHNOLOGY & ENGINEERING -- Material Science; Electronic books